Dendrimer nanoarchitectures for cancer diagnosis and anticancer drug delivery. Issue 2 (February 2017) - Sharma, Ashok Kumar; Gothwal, Avinash; Kesharwani, Prashant; Alsaab, Hashem; Iyer, Arun K.; Gupta, Umesh
Graphical abstract: Highlights: Dendrimers are efficient nanocarriers having biomedical and diagnostic application potentials. Dendrimers can be efficiently encapsulated with drugs by host–guest chemistry. The tailor-made surface functionality enables immense possibility for conjugation with bio-actives. Dendrimer nanoarchitectures are versatile carriers for cancer diagnosis, imaging and therapy. Abstract : Dendrimers are novel nanoarchitectures with unique properties including a globular 3D shape, a monodispersed unimicellar nature and a nanometric size range. The availability of multiple peripheral functional groups and tunable surface engineering enable the facile modification of the dendrimer surface with different therapeutic drugs, diagnostic agents and targeting ligands. Drug encapsulation, and solubilizing and passive targeting also equally contribute to the therapeutic use of dendrimers. In this review, we highlight recent advances in the delivery of anticancer drugs using dendrimers, as well as other biomedical and diagnostic applications. Taken together, the immense potential and utility of dendrimers are envisaged to have a significant positive impact on the growing arena of drug delivery and targeting. Abstract : Dendrimers are promising, efficient and smart nanocarriers with applications not only in drug delivery and targeting, but also in diagnosis. Host–guest chemistry, hyperbranched architecture and tailor-made surfaces make numerous surface-engineered dendrimer nanoarchitectures possible.